MODAL SOSIAL IBU HAMIL DALAM PROGRAM PENDAMPINGAN KADER - Ani Sukarsih Ani Sukarsih; Pulung Siswantara Pulung Siswantara (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2016)
Assistance for pregnant mother is one out of many government’s programs to reduce MaternalMortality Rate (or MMR) and Infant Mortality Rate (or IMR). This program is being particularly focusedon high-risk group of pregnant mothers, is a kind of fi eld activity to improve the welfare of the mother.Assistance itself in the implementation can not be separated from social capital. Assistance providedto pregnant mothers by health cadres itself is a manifestation of active roles in the community in whichthe cadres play continuous role in interaction. The purpose of this study was to analyze social capitalin ‘assistance for pregnant mother’ program. The study applied cross-sectional study design with aquantitative approach on as many as 35 pregnant mothers who were included in “assistance for pregnantmother” in Surabaya. Sampling was carried out using cluster random sampling. The independentvariables were the confi dence, norms and network while the dependent one was assistance for pregnantmother. Data analysis was performed using Spearman correlation test. The results showed that as manyas 21 respondents (or 60.0%) had high levels of social capital, 20 respondents (57.1%) had a moderatelevel of trust towards the cadres as a mentor, 29 respondents (82.9%) thought to have owned norms thatwere supporting assistance for pregnant mother and 14 respondents (40.0%) thought that their networkswere supporting the assistance. Spearman test indicated that no relationship was existed between socialcapital and assistance for pregnant mother, elements in social capital that had a relationship with theassistance for pregnant mother were the trust and norms.Keywords: Social capital, Assistance program, pregnant mother